Manhattan Transfer - Dos Passos, John, 1896-1970 (Salt Lake City, UT : Project Gutenberg, 2023)
"Manhattan Transfer" by John Dos Passos is a novel published in 1925. It captures the transformation of New York City from the Gilded Age to the Jazz Age through overlapping stories of diverse characters struggling to survive in the metropolis. Using experimental techniques inspired by Joyce and Eliot, Dos Passos creates a fragmented portrait of urban life$1 (Ba restless, merciless city teeming with strivers, winners, and losers. Their intersecting tales reveal the consumerism and social indifference of modern Manhattan. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Manhattan_Transfer_(novel)
Release date is 2023-10-11
Carol Brown, Emmanuel Ackerman and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: New York (N.Y.) -- Fiction; Psychological fiction; Social problems -- Fiction; Immigrants -- Fiction; Rich people -- Fiction; Manhattan (New York, N.Y.) -- Fiction